2018
DOI: 10.31351/vol27iss2pp115-122
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Investigation of Corchorus olitorius L. Leaves Cultivated in Iraq and it’s In Vitro Antiviral Activity

Abstract: The aim of our study was to investigate the antiviral activity of the Corchorus olitorius family Tiliaceae cultivated in Iraq against measles virus, and to demonstrate an overview about chemical constituents and pharmacological activity of Corchorus olitorius L. About150 gm Leaves of Corchorus. olitorius were defatted by maceration in hexane for 24 hrs. The defatted plant materials were subjected for extraction after filtration using Soxhlet apparatus, with aqueous methanol 85% as a solvent extraction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In a study reported previously, alkaloids, saponins, and flavonoids were detected in leaves of C. olitorius which correlates with the result of the present study (48). The present study also agrees with previous studies for the detection of flavonoids, alkaloids, and saponins in the leaf of C. olitorius (49,50). In another study on Jute whole plant, only flavonoids were detected with the absence of alkaloids and saponins in the ethyl acetate extract (51).…”
Section: Phytoconstituents Of Elecsupporting
confidence: 93%
“…In a study reported previously, alkaloids, saponins, and flavonoids were detected in leaves of C. olitorius which correlates with the result of the present study (48). The present study also agrees with previous studies for the detection of flavonoids, alkaloids, and saponins in the leaf of C. olitorius (49,50). In another study on Jute whole plant, only flavonoids were detected with the absence of alkaloids and saponins in the ethyl acetate extract (51).…”
Section: Phytoconstituents Of Elecsupporting
confidence: 93%
“…In vitro antiviral activity of Corchorus olitorius L. leaves methanolic extract against measles virus has been reported (Hasan & Kadhim, 2018). In vitro antiviral activity of Irvingia gabonensis extract against human immunodeficiency virus (HIV) has been reported (Abdurahman et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary phytochemical analysis was carried out for methanolic fraction using Mayer's reagent (alkaloids), 5% ethanolic KOH (flavonoids), FeCl3 (tannins), foam test for saponins, Benedict's test for sugars (17,18) , and Ninhydrin test for proteins (19) .…”
Section: Preliminary Chemical Testsmentioning
confidence: 99%